An independent validation of a gene expression signature to differentiate malignant melanoma from benign melanocytic nevi. Issue 4 (21st October 2016) - Clarke, Loren E.; Flake, Darl D.; Busam, Klaus; Cockerell, Clay; Helm, Klaus; McNiff, Jennifer; Reed, Jon; Tschen, Jaime; Kim, Jinah; Barnhill, Raymond; Elenitsas, Rosalie; Prieto, Victor G.; et al.
Abstract : BACKGROUND: Recently, a 23‐gene signature was developed to produce a melanoma diagnostic score capable of differentiating malignant and benign melanocytic lesions. The primary objective of this study was to independently assess the ability of the gene signature to differentiate melanoma from benign nevi in clinically relevant lesions. METHODS: A set of 1400 melanocytic lesions was selected from samples prospectively submitted for gene expression testing at a clinical laboratory. Each sample was tested and subjected to an independent histopathologic evaluation by 3 experienced dermatopathologists. A primary diagnosis (benign or malignant) was assigned to each sample, and diagnostic concordance among the 3 dermatopathologists was required for inclusion in analyses. The sensitivity and specificity of the score in differentiating benign and malignant melanocytic lesions were calculated to assess the association between the score and the pathologic diagnosis. RESULTS: The gene expression signature differentiated benign nevi from malignant melanoma with a sensitivity of 91.5% and a specificity of 92.5%. CONCLUSIONS: These results reflect the performance of the gene signature in a diverse array of samples encountered in routine clinical practice. Cancer 2017;123:617–628. © 2016 Myriad Genetics, Inc. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. Abstract : A 23‐gene signature has recently been developed to differentiate malignant and benign melanocytic lesions. This study shows that the gene expression signature differentiates benign nevi from malignant melanoma with a sensitivity of 91.5% and a specificity of 92.5% in comparison with a triple‐concordant histopathologic review.